Seismic Performance Evaluation of Reinforced Concrete Elevated Intze Tank Using Non Linear Time History Analysis - Baral, Prakash (Madhesh Journal of Interdisciplinary Research, 2026)
Elevated Reinforced Concrete Intze tanks play a crucial role in water supply infrastructure and are expected to run effectively during and after seismic events. The observations from pervious earthquakes indicate that these structures are highly vulnerable to damage due to flexibility of their staging systems, the substantial mass of stored water, and the complex interaction between fluid and the structure. This thesis investigates the seismic response of an RC elevated Intze tank through non linear time history analysis (NLTHA). A detailed three-dimensional finite element model is developed using SAP 2000, in which the impulsive and convective components of liquid masses are also modeled. Appropriate earthquake ground motion records are selected, scaled and applied to evaluate the dynamic response of Intze tanks with different capacity (300 cum, 600 cum and 1000 cum) for three tank fill conditions (empty, half filled and full filled). The performance of the tank is assessed based on parameter displacement response. The vulnerability of the tank is assessed through fragility curves obtained from the data of incremental non linear time history analysis. The study concludes that the seismic vulnerability of RC Elevated Intze tanks increases with increase in storage capacity and volume of water stored in the tank at the time of seismic event.